2016
DOI: 10.1038/srep29040
|View full text |Cite
|
Sign up to set email alerts
|

A Structure-free Method for Quantifying Conformational Flexibility in proteins

Abstract: All proteins sample a range of conformations at physiologic temperatures and this inherent flexibility enables them to carry out their prescribed functions. A comprehensive understanding of protein function therefore entails a characterization of protein flexibility. Here we describe a novel approach for quantifying a protein’s flexibility in solution using small-angle X-ray scattering (SAXS) data. The method calculates an effective entropy that quantifies the diversity of radii of gyration that a protein can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 60 publications
(87 reference statements)
6
53
0
6
Order By: Relevance
“…To quantify the difference in conformational entropy of the peptide chains in solution and in the aggregate, we compared the ensembles in terms of their RgD entropy, a metric recently introduced by Burger et al to quantify the entropy of IDP ensembles. 33 The RgD entropy of aggregated chains (2.254) is 25% higher than that of the solution ensemble (1.808) ( Fig. S8), indicating a significant increase of conformational entropy upon aggregation.…”
Section: Peptide Chain Dimensions Before and After Self-assemblymentioning
confidence: 94%
“…To quantify the difference in conformational entropy of the peptide chains in solution and in the aggregate, we compared the ensembles in terms of their RgD entropy, a metric recently introduced by Burger et al to quantify the entropy of IDP ensembles. 33 The RgD entropy of aggregated chains (2.254) is 25% higher than that of the solution ensemble (1.808) ( Fig. S8), indicating a significant increase of conformational entropy upon aggregation.…”
Section: Peptide Chain Dimensions Before and After Self-assemblymentioning
confidence: 94%
“…By contrast, the plots for the DBL3x-DBL6ε and DBL4ε-DBL6ε contain peaks that are shifted to longer qRg (1.8-1.95), indicative of a more elongated molecule. In addition, the plots for DBL3x-DBL6ε and DBL4ε-DBL6ε contain a shoulder at qRg ~4.9 and qRg ~4 respectively, and return to zero at qRg ~10, characteristic of proteins containing spatially distinct modules (54).…”
Section: Saxs Analysis Suggests That the Var2csa Ectodomain Is Compactmentioning
confidence: 98%
“…It has been observed that, for compact and globular (i.e., spherical) proteins, the variation of k 2 I c (k) with k is distinctly different and stronger than for ones in the partially disordered and/or unfolded states. 69,70 Specifically, a globular protein in the folded state exhibits an approximate semi-circular variation of k 2 I c (k) with k, which gradually dissipates or flattens out as the degree of structural disorder increases and the protein becomes partially disordered by unfolding itself. Following this observation, one may expect that the shape-dependence of the scattering intensity on a Kratky plot would be more pronounced for spherical voids than that for long cylindrical or highly elongated ellipsoidal voids (see Refs.…”
Section: Effect Of Void Shapes On Saxs: Kratky Plots For A-simentioning
confidence: 99%